Barack Obama’s Iowa caucuses rhetoric - Gunawan, Samuel (citeus, 2011)
This paper is to explore the depth of Barac Obama’s rhetoric in his Iowa Caucuses Speech: “Our Time for Change has Come”. Obama displayed his outstanding rhetorical craftsmanship to drive irresistibly his power of persuasion in the earliest Democratic Caucuses in the whitest state of Iowa that gave him a victory; thus the speech underscored the ground-breaking messages to the rest of the nation that America was ripe for an African-American President.